A Self-Tester for Linear Functions over the Integers with an Elementary Proof of Correctness - Devadas, Sheela; Rubinfeld, Ronitt (Theory of computing systems, 2016)
We present simple, self-contained proofs of correctness for algorithms for linearity testing and program checking of linear functions on finite subsets of integers represented as n -bit numbers. In addition we explore a generalization of self-testing to homomorphisms on a multidimensional vector space. We show that our self-testing algorithm for the univariate case can be directly generalized to vector space domains. The number of queries made by our algorithms is independent of domain size.